A single ascending dose study in healthy volunteers to assess the safety and PK of LY3372689, an inhibitor of O‐GlcNAcase (OGA) enzyme: Human/Human trials: Anti‐tau. (7th December 2020) - Kielbasa, William; Phipps, Krista M; Tseng, James; Natanegara, Fanni; Cheng, Eden; Monk, Scott A.; Bundgaard, Christoffer; Kevin, Donnelly B.; Nuthall, Hugh Norman; McDonald, Nicholas; Lindsay‐Scott, Peter; Dreyfus, Nicolas; et al.
Abstract: Background: LY3372689, an O‐GlcNAcase (OGA) enzyme inhibitor, is being developed as a potential treatment for tauopathies, including Alzheimer's disease. OGA inhibition is proposed to delay the progression of tau‐related diseases by slowing the accumulation of hyper‐phosphorylated, insoluble tau filaments. Herein we report the first clinical study that assessed safety and pharmacokinetics (PK) of LY3372689 after single oral doses in healthy volunteers (HV). Method: The phase 1 clinical trial (NCT03819270) was a single ascending dose, randomized, crossover, placebo controlled, investigator‐ and subject‐blind study. Each HV received up to 3 escalating single doses of LY3372689 or placebo over 3 study periods with an approximately 7‐day follow‐up period after each dose, such that a total of 6 LY3372689 dose levels were evaluated. Safety was assessed by adverse events (AE), safety laboratories, electrocardiograms, vital signs, physical exams, and neurological exams. Plasma PK was assessed up to 48 hours after LY3372689 administration. Result: A total of 23 HV (15 males, 8 females; 22 – 63 years) participated in the study, of which 18 completed and 5 did not complete due to loss to follow up procedures or did not meet randomization criteria. LY3372689 was generally well tolerated up to the maximum dose administered. There were no serious AE reported and no subjects discontinued the study because of an AE. A total of 13 treatment‐emergent AE reported by 5 subjects considered as possibly related to study treatment were mostly mild in severity, and included pain of skin, headache, limb discomfort, pain in extremity, chest discomfort, muscle fatigue, nausea, and rash macular. The PK of LY3372689 supported daily dosing and was generally dose proportional based on AUC and Cmax . Conclusion: LY3372689 demonstrated an acceptable safety and PK profile following single oral doses of LY3372689 in HV, which supports further investigation of LY3372689 as a potential treatment for tauopathies.